Financial Planning for Female Micro-Entrepreneurs in Malaysia - Erna Setiany; Nurul Hidayah; Deden Tarmidi; Khozaeni Bin Rahmad; Afzal Izzaz Zahari (Universitas, 2025)
Female migrant workers and Indonesian-descent micro-entrepreneurs in Malaysia face practical constraints in financial literacy, household–business cash-flow separation, and cross-border financial planning. This international joint community service—organized by Universitas Mercu Buana (UMB) with PERMAI Pulau Pinang and Universiti Sains Malaysia (USM)—delivered a contextualized training on budgeting, saving, and simple record-keeping for Indonesian communities in Pulau Pinang. The method combined partner mobilization, needs scoping, a face-to-face workshop, and a post-activity focus group discussion to inform sustainability steps. Thirty-three participants attended on 27 April 2025 at Yayasan An-Nahdhoh. Immediate outcomes included clearer understanding of household budgeting, the importance of separating personal and micro-business cash flows, and better coordination of remittances with families in Indonesia. Public outputs (video and mass-media coverage) enhanced accountability and replication potential. The findings suggest that simple, behaviorally oriented tools—delivered via trusted diaspora partnerships—can improve planning readiness and support micro-enterprise resilience